Why is it necessary to declare the Strait of Gibraltar an environmental control area? - Vanessa Durán-Grados (Annals of Limnology and Oceanography - Peertechz Publications, 2022)
Air pollution remains one of the most sensitive and harmful environmental concerns. According to a recent report 1 published by the World Health Organisation (WHO) [1] and the Organisation for Economic Co-operation and Development (OECD), in 2012, ambient air pollution was still responsible for about 500 000 premature deaths in Europe.